Sejarah Eropa Pada Abad Ke -19 - Anis Masduqi (TASAMUH: Jurnal Studi Islam, 2016)
This article talks about the history of Europe in the 19th century ago to today’s that modern world was born. The revolution of 1848 has given a deadly blow at all forms of pre-Marxian socialism. In all countries, the revolution revealed how social classes are diverse in their actions. In June days of 1848, the shooting of the workers by the republican bourgeoisie in Paris finally revealed that the proletariat the socialist character. The liberal bourgeoisie was a hundred times more afraid of the independent movement of this class than any kind of reactionary movements. Liberals are cowards worship the reactionary groups. During the 18th century a variety of fundamental changes in the economy began to occur in the Western world. The changes are far-reaching that, ultimately changing the overall way of human life. This transformation process is known as “industrial revolution”. This movement was first evident in the UK, but in the mid-19th century it spread to Europe continental. Transformation in economic activity stemming from the industrial revolution was accompanied by the dismantling of economic theory. In line with the progress and pace of mankind in the fields of industry, the various roads have been done “in order to dominate the market and new targets, in order to throw their products. Tempers of polarization in the community, a group of owners of capital and working groups boast his achievements